Effect of anionic macromolecules on intestinal permeability of furosemide. (February 2015) - Valizadeh, Hadi; Fahimfar, Hadi; Ghanbarzadeh, Saeed; Islambulchilar, Ziba; Zakeri-Milani, Parvin
Abstract Context: Furosemide is an anionic molecule and has very low absorption in gastro intestinal tract. Objective: The aim of this study was to investigate the effect of anionic macromolecules on the intestinal permeability of Furosemide. Materials and methods: The intestinal permeability of Furosemide was determined using single-pass intestinal perfusion technique in rats. Briefly a jejunal segment of ∼10 cm was isolated and cannulated in both ends for inlet and outlet solution. The perfusate was collected every 10 min and samples were analyzed using the RP-HPLC method. Test samples containing furosemide and two anionic macromolecules, sodium carboxy methyl cellulose and sodium alginate, at different concentrations were used. Results: The obtained data showed that existence of Sodium carboxy methyl cellulose significantly increased the Peff values in all three investigated concentrations (p < 0.05) but sodium alginate only in concentrations <0.1% increased drug permeability. Discussion: It is concluded that the anionic macromolecules at specific concentrations could alter the permeability of anionic drugs across the biological membranes. Conclusions: Donnan phenomenon and chelating property of macromolecules could be attributed to the observed effect.